Kepedulian Mahasiswa dalam Pelestarian Lingkungan melalui Gerakan Kebersihan - Rommy Hardyansah; Mirabel Nabila Istiqomah; Didit Darmawan; Rahayu Mardikaningsih; Mila Hariani (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The purpose of this activity is to analyze the influence of the sustainable cleanliness movement on students' level of environmental awareness. Environmental conservation activities through the sustainable cleanliness movement conducted by students are carried out on campus. The sustainable cleanliness movement activities carried out by students on campus reflect the application of the Asset-Based Community Development (ABCD) method, which focuses on strengthening local assets such as skills, motivation, and student networks. Direct participation in activities such as waste collection and environmental education has been shown to significantly increase student engagement and foster social responsibility towards the environment. The implementation of these activities has also succeeded in instilling important values ​​such as environmental awareness and a spirit of cooperation. Given the positive impacts generated, it is highly recommended that similar activities be held regularly and periodically to raise awareness of the importance of environmental protection. The campus or student groups are encouraged to continue implementing the sustainable environmental cleanliness program for the ongoing benefits of all parties on campus.